Effects of Liquid Bio-Fertilizer on Plant Growth, Antioxidant Activity, and Soil Bacterial Community During Cultivation of Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Tran Yen Linh Le; Junkyung Lee; Su-Yeon Shim; Jiwon Jung; Soo-Ryang Kim; Sung-Ha Hong; Myung-Gyu Lee; Sun-Goo Hwang (Microorganisms)
This study investigated the effects of liquid bio-fertilizer (LBF) on the growth, antioxidant activity, soil properties, and soil microbial composition of Chinese cabbage (Brassica rapa L. ssp. pekinensis). The LBF application significantly enhanced vegetative growth by increasing the leaf length, leaf width, fresh weight, and dry weight. Additionally, antioxidant activity increased with rises in total phenolic and flavonoid contents. However, the per-unit antioxidant concentrations decreased, likely due to rapid biomass accumulation. Soil analysis showed improvements in pH, organic matter, and available phosphorus. Microbial analysis revealed that Acidobacteria enrichment was associated with enhanced nutrient cycling despite reduced overall microbial diversity. Transcriptomic analysis identified 445 differentially expressed genes with upregulation in the metabolism and photosynthesis-related pathways, suggesting improved nutrient assimilation and energy production. These findings demonstrate that LBF enhances plant growth and soil fertility while influencing microbial dynamics and gene expression.